A chitinase involved in the mycoparasitism of Trichoderma atroviride on aeciospores of Cronartium ribicola. Issue 4 (27th January 2022) - Li, Jing; Kong, Lei; Ma, Changle; Bao, Zeran; Zhang, Dengyun; Chen, Yuhui; Wang, Changming
Abstract: Trichoderma atroviride SS003 is a mycoparasite of Cronartium ribicola, and it has a significant destructive effect on rust aeciospores. Based on transcriptome sequencing results and qPCR validation, the expression of a chitinase gene named CHI10 was upregulated after induction for 24, 72 and 120 h. A 1.3‐kb cDNA of CHI10 was obtained by RT‐PCR from SS003 mycelium co‐cultured with the cell walls of the aeciospores for 24 h. After the prokaryotic expression of CHI10 gene in Escherichia coli, a recombinant 46.0 kD protein was obtained, and the target fusion protein was partially purified, which was shown to have destructive effects on the cell wall of aeciospores at 40–55°C. This chitinase may be associated with the mycoparasitism of T . atroviride on aeciospores of C . ribicola .